MAIN ASPECTS OF ANTHROPOGENIC IMPACT ON THE CURRENT ENVIRONMENTAL AND ECONOMIC STATE OF UKRAINE - POGREBNYAK, Andriy; BAZYK, Oleksandr; VISHNIKINA, Olena; ZINCHENKO, Heorhii; ROMANOV, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The effective fight against environmental pollution requires close cooperation between government organizations, scientific institutions, public organizations and business. It is necessary to develop and implement modern technologies to reduce emissions of pollutants, increase environmental awareness of the population, and also improve the legislative framework and regulatory mechanisms. In addition, it is important to conduct further scientific research for a deeper understanding of environmental problems and the development of effective strategies for solving them. Solving the problem of pollution of industrial origin requires the modernization of industrial enterprises, the introduction of the latest technologies for the purification of emissions, as well as the improvement of the monitoring and control system for emissions. Special attention should be paid to enterprises of the metallurgical and chemical industry, which are the main sources of heavy metals and toxic substances. The energy sector needs a transition to more ecologically clean sources of energy, in particular, an increase in the number of productions from generation due to the use of natural, renewable sources. The article classifies the main sources and consequences of ecological burden on the environment, analyzes the works of leading Ukrainian scientists, devoted to the shortcomings associated with the imperfection of Ukrainian environmental legislation, the ecological state of Ukraine and its population, economic problems caused by pollution of socio-ecological economic systems. The presented work is the first part of a study devoted to the comparative analysis of ecological, economic and social consequences of pollution of the territories of Ukraine in peacetime and wartime.